Skeletal Muscle Protein Composition Adaptations to 10 Weeks of High-Load Resistance Training in Previously-Trained Males - Vann, Christopher G.; Osburn, Shelby C.; Mumford, Petey W.; Roberson, Paul A.; Fox, Carlton D.; Sexton, Casey L.; Johnson, McLelland-Rae; Johnson, Joel S.; Shake, Jacob; Moore, Johnathon H.; Millevoi, Kevin; Beck, Darren T.; et al. (Frontiers in Physiology, 2020)
While high-load resistance training increases muscle hypertrophy, the intramuscular protein responses to this form of training remains largely unknown. In the current study, recreationally resistance-trained college-aged males (N=15; mean±SD: 23±3 years old, 6±5 years training) performed full-body, low-volume, high-load (68%-90% of one repetition maximum (1RM)) resistance training over 10 weeks. Back squat strength testing, body composition testing, and a vastus lateralis biopsy were performed before (PRE) and 72 hours after the 10-week training program (POST). Fiber type-specific cross-sectional area (fCSA), myofibrillar protein concentrations, sarcoplasmic protein concentrations, myosin heavy chain and actin protein abundances, and muscle tissue percent fluid were analyzed. The abundances of individual sarcoplasmic proteins in 10 of the 15 participants were also assessed using proteomics. Significant increases (p<0.05) in type II fCSA and back squat strength occurred with training, although whole-body fat-free mass paradoxically decreased (p=0.026). No changes in sarcoplasmic protein concentrations or muscle tissue percent fluid were observed. Myosin heavy chain protein abundance trended downward (-2.9±5.8%, p=0.069) and actin protein abundance decreased (-3.2±5.3%, p=0.034) with training. Proteomics indicated only 13 sarcoplasmic proteins were altered with training (12 up-regulated, 1 down-regulated, p<0.05). Bioinformatics indicated no signaling pathways were affected, and proteins involved with metabolism (e.g., ATP-PCr, glycolysis, TCA cycle, or beta-oxidation) were not affected. These data comprehensively describe intramuscular protein adaptations that occur following 10 weeks of high-load resistance training. Although previous data from our laboratory suggests high-volume resistance training enhances the ATP-PCr and glycolytic pathways, we observed different changes in metabolism-related proteins in the current study with high-load training.